Revised lithostratigraphy of fluvio-lacustrine sediments comprising northern Kathmandu basin in central Nepal - Sakai, Tetsuya; Gajurel, Ananta P; Upreti, Bishal N; Tabata, Hideo; Ooi, Nobuo; Kitagawa, Hiroyuki (Journal of Nepal Geological Society, 2012)
The lithostratigraphic classification of basin deposits in the northern Kathmandu valley is revised on the basis of detailed lithological and facies analyses, radiocarbon dating, and previously reported palaeomagnetic polarity data. The basin deposits are divided into the Dharmasthali, Kalimati, Gokarna, Thimi, Tokha, and Patan Formations, respectively in an ascending order. Only the Kalimati Formation is distributed in the central basin, and appears to be the distal equivalent of the other formations. The Tokha Formation, firstly defined as all sediments in the northwest basin, is reclassified here as the Gokarna Formation (50–34 ka) below 1355 m and the unconformably overlying Tokha Formation (19–14 ka). The Gokarna Formation is characterised by two widely traceable thick black silt beds. The Thimi Formation is dated at 33–24 ka and the Patan Formation at 14–10 ka. The depositional time of the Kalimati Formation spans all of these periods and those of the older deposits distributed in the southern Kathmandu valley. Absolute age data could not be obtained for the newly defined Dharmasthali Formation. Previous magnetostratigraphic analyses detected intervals of reverse polarity, corresponding to the accumulation time prior to 780 ka, which is probably equivalent to the Pliocene to Lower Pleistocene successions (viz., the Tarebhir, Lukundol, and Itaiti Formations) distributed in the southern Kathmandu valley Jour. Nep. Geol. Soc., Vol. 37, 2008, 25-44